Obtaining and Properties of Hexaferrite BaFe12O19 for High-coercivity Permanent Magnets and Substrates Microstrip Microwave Devices of mm-Range - V.G. Kostishyn; V.V. Korovushkin; D.N. Chitanov; Yu.M. Korolev (Журнал нано- та електронної фізики)
In the work by ceramic technology produced samples isotropic and anisotropic polycrystalline hexaferrite BaFe12O19 and investigated their properties. It is shown that as the permanent magnets can be used both types of samples, whereas for substrates microstrip microwave devices mm-range expedient to use only anisotropic polycrystalline hexaferrite BaFe12O19.